The Influence of Compensation And Leadership Style on Employee Performance Through Work Motivation as an Intervening Variable - Rizal, Hafidhur (Formosa Journal of Sustainable Research, 2024)
The study's objective is to demonstrate how leadership style and compensation affect worker performance, with job motivation acting as a mediating factor. Quantitative research comprised studies done on PNM Lamongan Branch personnel. The sampling technique employed the total sample, with 87 employees serving as samples. A questionnaire is the tool used in the data collection process. The Likert scale is the measurement scale that is employed in the survey. This study used the Smart PLS 4 application to do structural equation modeling as its analysis approach. The findings of the study indicate that employee motivation and performance are positively impacted by pay, positively impacted by leadership style, and positively impacted by job motivation. The The findings of the indirect effect demonstrate that leadership style and salary both have an impact on employee performance through job motivation